Efficiency of Use of Labor Resources in Production Enterprises - Komilova Mukammal Shavkatovna; Mirzayev Zafar Abdialimovich (Research Parks Publishers, 2022)
The article developed economically based proposals and recommendations for the provision of labor resources and effective use of production enterprises.